Expanding phenotype of De Novo mutations in GNAO1: four new cases and review of literature - Schorling, David; Evers, Christina; Hinderhofer, Katrin (Neuropediatrics, 2017)
Mutations in GNAO1 (guanine nucleotide-binding protein, alpha-activating activity polypeptide O) were recently identified as being causative for early epileptic encephalopathy. Since then approximately 27 patients with severe developmental delay and different neurological phenotypes for epilepsy and involuntary movement disorder have been reported. We report four additional patients with mutations in GNAO1 including a report of siblings of different sex harboring the same de novo mutation (c.736G > A, p.Glu246Lys) but showing differences in phenotype with pronounced dystonia in the boy and epilepsy in his sister. Another de novo mutation in GNAO1 (c.607G > A, p.Gly203Arg) was identified in two unrelated girls with severe epilepsy. Both girls later also developed severe dystonia with severe nonepileptic spasms. An extensive review of published cases revealed that epilepsy was reported in only one male patient so far. Thus it appears possible that epilepsy is a sex-dependent phenotypic feature of GNAO1-related diseases.